THREE DIMENSIONAL MODELING WITH GEOSTATISTICAL METHODE FOR RESERVOIR CHARACTERIZATION AND UNCERTAINTY ANALYSIS CASE STUDY : FANZA FIELD , SOUTH SUMATRA BASIN - Iswachyono, Tri
Fanza field was first discovered in 1997 with the content of gas, located in South Sumatra Basin. Act as a reservoir rock is limestone from Baturaja Formation. At this time the field is still in development stage, so it requires a three-dimensional modeling to optimize hydrocarbon recoverable reserves. Three-dimensional modeling is done by integrating the sub-surface data such as seismik data, well log data and core data. The distribution of reservoir parameters will be done by applying geostatistical method. Geostatistical method could captured the reservoir heterogeneity and could simulate quantitatively with the more detailed and more accurate by integrating various data sources (geology, geophysics, production, reservoir) from a variety of scales. Further sensitivity analysis of parametric properties to determine the parameters of the most significant contributions to the reserve calculations. Also done the analysis of the probability of the reserve calculation to determine the distribution that will be used for further field development planning. Application geostatistic method for modeling three dimensional reservoir on the Fanza Field showed good results. It is proved by this method is capable to predict some of the conditions of the reservoir with a relatively high degree of accuracy through validation of statistical methods and well-blind method. Uncertainty and sensitivity analysis of parameters for the initial gas volume and volumetric calculations give the results of the porosity parameter as the parameter uncertainty effects are most significant to the final outcome of the calculation of volumetric OGIP Fanza Field. From the results of calculations using Monte Carlo simulation method we got the probability of the value that obtained volumetric OGIP Fanza Field that can use for planning and design of future field development.